A real-time model-free reconfiguration mechanism for fault-tolerance: Application to a hydraulic process - Yame, J.J.; Sauter, D. (2008 10th International Conference on Control Automation Robotics and Vision, 2008)
In this note, we present a real-time model-free reconfiguration mechanism to achieve fault-tolerant control (FTC) and we show the feasibility of this technique with a simple hydraulic plant subject to actuators faults. The main feature of the reconfiguration technique is that it relies solely on the data generated by the actual plant and on the (control) specifications given by a performance functional. The resulting FTC system does not embed any on-line model-based fault detection and isolation (FDI) algorithms, and therefore such closed-loop system gets rid off the drawbacks of FDI-based fault-tolerant controllers.